Risk and outcome of COVID-19 infection in sarcoidosis patients: results of a self-reporting questionnaire - Baughman, Robert P.; Lower, Elyse; Buchanon, Mindy; Rottoli, Paola; Drent, Marjolein; Sellares, Jacobo; Terwiel, Michelle; Elfferich, Marjon; Francesqui, Joel; Barriuso Cabrerizo, Maria Rita; Sweiss, Nadera; Martone, Filippo; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: It has been suggested that sarcoidosis patients, especially those on immunosuppressive medications, are at increased risk for COVID-19 infection and more severe disease.Methods: A questionnaire was developed in four languages (English, Dutch, Italian, and Spanish). The questionnaire queried whether patients had been infected with COVID-19 and outcome of the infection. Risk factors for COVID-19 infection were collected.  Results: A total of 5200 sarcoidosis patients completed the questionnaire with 116 (2.23%) reporting infection and 18 (15.8%) required hospitalization. Increased hazard ratio (HR) for COVID-19 infection were seen for those with a COVID-19 infected roommate (HR=27.44, p